A case of multiple solitary neurofibromas located in the hypopharynx and cervical esophagus. Issue 1 (24th August 2022) - Kazu, Hamada; Yuzo, Shimode; Yoshiyuki, Hata; Hiroaki, Kunou; Rika, Kobayashi; Kazuhiro, Matsunaga; Ken, Kawaura; Tsuyoshi, Mukai; Hidekazu, Kitakata; Tohru, Itoh; Masashi, Okuro; Sohsuke, Yamada
Abstract: A 50‐year‐old female was admitted to our hospital because of mild throat discomfort. Esophagogastroduodenoscopy demonstrated multiple 2–3 mm diameter whitish granules in her hypopharynx and cervical esophagus. Based on biopsy specimens, we considered the lesions to represent normal tissue or very mild mucosal dysplasia. However, S‐100 immunohistochemical staining 3 years later led to a diagnosis of multiple solitary neurofibromas located in the hypopharynx and cervical esophagus. Histological finding characteristics of neurofibroma were present in 72.7% of hypopharyngeal biopsy specimens and 33.3% of esophageal specimens. When diagnosing neurofibroma, it is important to perform biopsies at multiple locations and at different times and to enlist the cooperation of endoscopists and pathologists for immunohistochemical staining with S‐100.